2018
DOI: 10.1111/ene.13538
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of detecting atrial fibrillation in stroke patients: results from the TRACKAF Study

Abstract: A combination of SRA and ICM is a promising strategy to detect occult AF. SRA is reliable in predicting incident AF with a high negative predictive value. Thus, SRA may serve as a cost-effective pre-selection tool identifying patients at risk for AF who may benefit from further cardiac monitoring by ICM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The mean/median elapsed time from IS/TIA onset to cardiac monitoring implantation ranged from 3 to 174 days, while the mean/median ICM duration ranged from 180 to 1,080 days (Table 1). Included studies were generally found to have a low risk of bias (Supplementary Table 3), except in cases not clearly stating consecutive enrollment of patients [23,26,27,39,44-47], exclusion of AF with electrocardiogram or short-term non-invasive Holter monitoring prior to ICM impantation [21,33], or no adjudication of ICM recordings by experienced cardiologists [26-29,33,41,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…The mean/median elapsed time from IS/TIA onset to cardiac monitoring implantation ranged from 3 to 174 days, while the mean/median ICM duration ranged from 180 to 1,080 days (Table 1). Included studies were generally found to have a low risk of bias (Supplementary Table 3), except in cases not clearly stating consecutive enrollment of patients [23,26,27,39,44-47], exclusion of AF with electrocardiogram or short-term non-invasive Holter monitoring prior to ICM impantation [21,33], or no adjudication of ICM recordings by experienced cardiologists [26-29,33,41,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Other AF detection algorithms have already been tested and seem to be useful, but in our opinion need improvements. 4,[33][34][35] The detection methods for some of these biomarkers are already available and they can potentially be used routinely in the clinical assessment of cryptogenic stroke and TIA patients. 22 The results from our pilot study indicate that multiple proteins may potentially be used as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, the same AA was also used in patients with cryptogenic stroke to select those who may benefit from prolonged cardiac monitoring afforded by an implantable device. 32 In a comparable approach, a recent study demonstrated that application of an artificial intelligence algorithm on 12-lead ECG in sinus rhythm was able to select patients at high risk for developing AF and might thereby not only decrease the diagnostic workload of ECG analysis but also increase the diagnostic yield of AF. 33 Moreover our data support a more intensified screening for pAF in patients with increased age, previous administration of intravenous thrombolysis or more severe stroke symptoms at admission, as measured by the NIHSS.…”
Section: Discussionmentioning
confidence: 99%